Hubungan Pengetahuan Dan Sikap Ibu Rumah Tangga Tentang HIV/AIDS Dan VCT Dengan Keinginan Melakukan Tes VCT Di Wilayah Kecamatan Kartasura - Prasetya, Aria Dwi; , Anisa Catur Wijayanti, SKM., M.Epid (2016)
Indonesia is one of the countries in Asia that have HIV vulnerability due to the impact of changes in economic and social life. According to KPA of Central Java in 2015 cases of HIV / AIDS in Central Java, the majority occur in the productive age. Based on the type of work, housewife ranked second as much as 18.6%. This suggests that HIV has spread in the community that had been considered not high risk group. Knowledge and attitudes become factors that may affect the desire VCT. The purpose of this study was to determine the relationship to knowledge and attitudes housewife on HIV / AIDS and VCT with the desire to do VCT in the region Kartasura. The research method used is observational design with cross-sectional approach. The population in this study is a housewife who resides in the district Kartasura totaling 163 people. The sampling technique used in this study is Proportionate Stratified Random Sampling with 163 people as samples. Statistical test uses the Fisher exact and chi-square. There is a relationship with the desire of knowledge in the area Kartasura VCT (p value = 0.004). There is a relationship with the attitude desires in the region Kartasura VCT (p value = 0.002).